Impact of Per Capita Health Expenditure on Child Health Outcomes in Nepal - Paudel, Manisha (Journey for Sustainable Development and Peace Journal, 2024)
This paper explores the relationship between child health outcomes and per capita health investment in Nepal, using key indicators such as child mortality rate, stunting, skilled birth attendance, and appropriate treatment for acute respiratory infections. The study utilizes the data primarily from the World Bank and the Ministry of Finance in Nepal. The study adopts quantitative analysis techniques, including correlation and regression analysis, to assess the impact of health investment on child health outcomes. The results show that increased per capita health expenditure is positively correlated with improved child health outcomes which shows linear growth in different variables if compared with the per capita investment done in health. There is a negative correlation between per capita health expenditure and child mortality under 5 years of age and this is evidenced that increased per capita health expenditure reduces the child mortality among under 5 years of children. Thus, the study aims to highlight the importance of allocating resources in policy reforms, capacity building and allocating resources in the health sector. The study also incorporates relevant resources from scholarly articles and academic literature to provide a comprehensive understanding of the topic and support the analysis regarding the relationship between per capita health investment and child health outcomes.